The Impact of Advertising Attractiveness, Event Promotion, and Discount Prices on Product Purchase Decisions on Instagram @promomedan.id - Hendra Jonathan Sibarani; Anjeli; Justin Adi Putra Pasaribu (Journal of Research in Business, Economics, and Education, 2021)
abstract